2021
DOI: 10.1002/acr.24200
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab for the Treatment of Giant Cell Arteritis

Abstract: Objective To evaluate the efficacy and safety of ustekinumab (UST) in giant cell arteritis (GCA). Methods We conducted a prospective, open‐label trial of UST in patients with active new‐onset or relapsing GCA. Active disease was defined as the presence of GCA symptoms and elevation of erythrocyte sedimentation rate (ESR) or C‐reactive protein (CRP) level within 6 weeks of baseline. All patients received a 24‐week prednisone taper and subcutaneous UST 90 mg at baseline and at weeks 4, 12, 20, 28, 36, and 44. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 20 publications
0
33
0
3
Order By: Relevance
“…Ustekinumab, a monoclonal antibody that inhibits both IL-12 and IL-23 signaling by binding to the common p40 subunit, has been tested in patients with GCA and Takayasu arteritis ( 114 , 115 ). A prospective, open-label trial of ustekinumab in 13 patients with active new-onset or relapsing GCA was prematurely closed because patients could not reach prednisone-free remission ( 116 ). Blocking IL-12/IL-23 should interfere with the differentiation program of naïve into memory/effector T cells, a process that may precede the onset of vasculitis.…”
Section: From Bench To Bedside: Potential Therapeutic Targets In Gcamentioning
confidence: 99%
“…Ustekinumab, a monoclonal antibody that inhibits both IL-12 and IL-23 signaling by binding to the common p40 subunit, has been tested in patients with GCA and Takayasu arteritis ( 114 , 115 ). A prospective, open-label trial of ustekinumab in 13 patients with active new-onset or relapsing GCA was prematurely closed because patients could not reach prednisone-free remission ( 116 ). Blocking IL-12/IL-23 should interfere with the differentiation program of naïve into memory/effector T cells, a process that may precede the onset of vasculitis.…”
Section: From Bench To Bedside: Potential Therapeutic Targets In Gcamentioning
confidence: 99%
“…When data from GCA and TAK studies were combined in a meta-analysis, the only non-HLA SNP that reached significance was in IL12B, encoding the p40 portion of the IL-12 (p35p40)/IL-23 (p19p40) heterodimeric proteins that is shared by both cytokines ( 47 ). Yet, clinically targeting p40 with ustekinumab in two open-label trials has shown mixed results in GCA ( 49 , 50 ). Collectively, epidemiologic data emphasizes the importance of old age, female sex, and genetics with GCA though how these factors contribute to disease pathogenesis remains largely unclear.…”
Section: Epidemiologymentioning
confidence: 99%
“…Notably, of 10 patients with LV disease in this study, eight underwent reimaging by CT angiography, which demonstrated not only a halt to further vascular damage but improvement of wall thickening in all patients and complete resolution in four ( 49 ). In the American trial, both newly diagnosed and relapsing patients were recruited and all patients were required to end GC at 6 months, resulting in clinical flare across the majority of patients with elevated inflammatory markers and PMR symptoms; though data was not shown for relapse between newly diagnosed vs/ relapsing patients they were stated not to be different ( 50 ). Vascular imaging follow up was not reported ( 50 ).…”
Section: Pathophysiology Of Gcamentioning
confidence: 99%
See 1 more Smart Citation
“…A second prospective, single centre, open-label pilot study was subsequently performed. 58 This study enrolled both new onset and relapsing GCA patients with active disease. Diagnosis required either a positive temporal artery biopsy or evidence of large vessel vasculitis on imaging.…”
Section: Il-12/il-23 Inhibition – Ustekinumabmentioning
confidence: 99%